Descender. Book three, Singularities - Lemire, Jeff (Image Comics, 2016)
"One young robot's struggle to stay alive in a universe where all androids have been outlawed and bounty hunters lurk on every planet. A rip-roaring and heart-felt cosmic odyssey that pits humanity against machine, and world against world, to create a sprawling space opera from the creators of Trillium, Sweet Tooth, and Little Gotham. This third volume collects issues #12-16 of the best-selling, critically acclaimed series." --